2009
DOI: 10.1021/es900075q
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Rule-Based Model to Estimate Mercury Exchange for Three Background Biomes in the Continental United States

Abstract: Ecosystems that have low mercury (Hg) concentrations (i.e., not enriched or impacted by geologic or anthropogenic processes) cover most of the terrestrial surface area of the earth yet their role as a net source or sink for atmospheric Hg is uncertain. Here we use empirical data to develop a rule-based model implemented within a geographic information system framework to estimate the spatial and temporal patterns of Hg flux for semiarid deserts, grasslands, and deciduous forests representing 45% of the contine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 51 publications
6
26
0
1
Order By: Relevance
“…Subsequent models simply treated plant emission as a function of evapotranspiration rate (Xu et al, 1999;Bash et al, 2004;Gbor et al, 2006;Shetty et al, 2008). However, more recent measurements suggested that air-surface exchange of Hg 0 is largely bidirectional between air and plant and that growing plants act as a net sink (Ericksen et al, 2003;Stamenkovic et al, 2008;Hartman et al, 2009). Stable Hg isotope tracer studies have shown that Hg in soils cannot be translocated from roots to leaf due to the transport barrier at the root zone (Rutter et al, 2011b;Cui et al, 2014), suggesting that the source of Hg in the leaf is of atmospheric origin.…”
Section: Air-vegetation Hg 0 Exchangementioning
confidence: 99%
“…Subsequent models simply treated plant emission as a function of evapotranspiration rate (Xu et al, 1999;Bash et al, 2004;Gbor et al, 2006;Shetty et al, 2008). However, more recent measurements suggested that air-surface exchange of Hg 0 is largely bidirectional between air and plant and that growing plants act as a net sink (Ericksen et al, 2003;Stamenkovic et al, 2008;Hartman et al, 2009). Stable Hg isotope tracer studies have shown that Hg in soils cannot be translocated from roots to leaf due to the transport barrier at the root zone (Rutter et al, 2011b;Cui et al, 2014), suggesting that the source of Hg in the leaf is of atmospheric origin.…”
Section: Air-vegetation Hg 0 Exchangementioning
confidence: 99%
“…Eckley and Branfireun (2008) identified that flux increases with temperature and solar radiation and as a result, fluxes are higher during the daytime than at night and generally higher in the summer than in winter (Choi and Holsen, 2009a;Gabriel et al 2006;Eckley et al 2011); however some studies have also identified that lower solar radiation under deciduous canopies and lower soil moisture content results in lower summertime fluxes (Hartman et al 2009;Kuiken et al 2008). Because several studies have shown diel Hg o fluxes to generally follow a curve similar to solar elevation, measurements conducted only during daylight hours will greatly overestimate mean daily emissions (Engle et al 2001;Gabriel et al 2006;Gustin et al 2003 (Gustin et al 1999;Eckley et al 2010;Rolfhus and Fitzgerald, 2001 DFC measurements were available they were selected; however for some surfaces purge/trap data was only available and was applied for scaling.…”
Section: Introductionmentioning
confidence: 99%
“…To improve estimation of mercury emission from natural sources, a global database of GEM flux from different land covers and geogenic sources could be developed, similar to those done by Ericksen et al (2006) and Hartman et al (2009). Another way to approach this would be to do a literature review and compile papers that have identified dominant mechanisms and developed algorithms that can be applied in models (Eckley et al, , 2016Hartman et al, 2009). Dominating factors include soil concentration of Hg, solar radiation, temperature, soil moisture, and precipitation (Briggs an Gustin, 2013).…”
Section: Mercury Emissionmentioning
confidence: 99%